2020
DOI: 10.1002/hbm.24992
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant static and dynamic functional patterns of frontoparietal control network in antipsychotic‐naïve first‐episode psychosis subjects

Abstract: Psychotic disorders are disabling clinical syndromes characterized by widespread alterations in cortical information processing. Disruption of frontoparietal network (FPN) connectivity has emerged as a common footprint across the psychosis spectrum. Our goal was to characterize the static and dynamic resting‐state functional connectivity (FC) of the FPN in antipsychotic‐naïve first‐episode psychosis (FEP) subjects. We compared the static FC of the FPN in 40 FEP and 40 healthy control (HC) subjects, matched on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…QPP1 was selected as the template with the maximum sum, which reflects a combination of high strength and frequent occurrence. In humans, QPP1 is ~20s long (Majeed et al, 2011;Yousefi et al, 2018;Abbas et al, 2019a,b;Briend et al, 2020); hence, we preset the segment duration to 30 timepoints (21.6s). In the prior studies (Majeed et al, 2011;Yousefi et al, 2018;Abbas et al, 2019aAbbas et al, , 2019bBelloy et al, 2018aBelloy et al, , 2018b) the correlation threshold was set to 0.1 for the first three iterations of the main algorithm, and 0.2 for the remaining iterations; however, we increased this threshold to 0.2 for the first two iterations and 0.3 for the remaining iterations, mainly because of high quality and large dataset used here.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…QPP1 was selected as the template with the maximum sum, which reflects a combination of high strength and frequent occurrence. In humans, QPP1 is ~20s long (Majeed et al, 2011;Yousefi et al, 2018;Abbas et al, 2019a,b;Briend et al, 2020); hence, we preset the segment duration to 30 timepoints (21.6s). In the prior studies (Majeed et al, 2011;Yousefi et al, 2018;Abbas et al, 2019aAbbas et al, , 2019bBelloy et al, 2018aBelloy et al, , 2018b) the correlation threshold was set to 0.1 for the first three iterations of the main algorithm, and 0.2 for the remaining iterations; however, we increased this threshold to 0.2 for the first two iterations and 0.3 for the remaining iterations, mainly because of high quality and large dataset used here.…”
Section: Methodsmentioning
confidence: 99%
“…One of the recurring spatiotemporal patterns of activity is the quasiperiodic pattern (QPP), obtained by identifying and averaging similar segments of rsfMRI timeseries (Majeed et al, 2011(Majeed et al, , 2009. The primary QPP (QPP1) in humans is approximately 20 seconds in duration and involves a cycle of activation and deactivation of different brain areas with various phases; most prominently, the cortical areas recognized as the task positive network (TPN) exhibit the opposite phase relative to the cortical areas known as the task negative or default mode network (DMN) (Majeed et al, 2011;Yousefi et al, 2018;Abbas et al, 2019aAbbas et al, , 2019bBriend et al, 2020). Focal propagation of activity is also observed, for example, along the medial prefrontal cortex (Majeed et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…More focused analyses assessing the functional correlates of auditory hallucinations found that CV in schizophrenic subjects was reduced between the left auditory perception and speech-production brain areas [64]. Psychotic-like experiences CS [66] First episode psychosis Quasi-periodic patterns [67] High risk of psychosis CAPs [68] Clinical high risk of psychosis and early illness schizophrenia CS [69] 22q11 deletion syndrome iCAPs [70] Major depressive disorder MDD CS [33] MDD CS [71] MDD CS, CV [72] MDD Multilayer GA [73] First episode MDD, untreated CS [74] MDD in remission LEiDA [75] When focusing on hallucination severity, a dynamic GA revealed that nodal flexibility of the lateral occipital cortex was perturbed in people with schizophrenia, and this was related to symptom strength [65].…”
Section: Dynamic Approaches Have Been Leveraged To Study Behaviormentioning
confidence: 99%
“…Using dynamic conditional correlation, a framewise alternative to sliding window analysis (Box 2), a study showed that healthy subjects undergoing psychoticlike experiences spent more time in a state characterized by hypoconnectivity within the DMN, and hyperconnectivity within visual regions [66]. Moreover, measuring quasi-periodic patterns in participants with first-episode psychosis revealed hypoconnectivity in the frontoparietal network [67]. Similarly, a CAP analysis with an anterior insula seed demonstrated that individuals at high risk of psychosis have prolonged expression of a CAP that resembles the DMN, as well as decreased CAP switching, compared to healthy controls [68].…”
Section: Dynamic Approaches Have Been Leveraged To Study Behaviormentioning
confidence: 99%
“…Spatial patterns of dysconnectivity resemble those in unmedicated, chronic schizophrenia patients ( 71 ). When examining dynamic connectivity, we found that quasi-periodic patterns had a greater impact of fronto-parietal control network connectivity in first episode patients compared to controls, suggesting that brain network dynamics are already altered in this patient group ( 70 ). Taken together, connectivity alterations are clearly already present in medication-naïve patients, which is consistent with the hypothesis that brain network dysconnectivity is a core feature of the illness ( 73 75 ).…”
Section: Key Scientific Questions In Neuroimaging Research In Schizopmentioning
confidence: 95%